1995
DOI: 10.1139/f95-817
|View full text |Cite
|
Sign up to set email alerts
|

Ecological effects of blooms of filamentous green algae in the littoral zone of an acid lake

Abstract: Ecological effects of blooms of filamentous green algae (FGA) were studied in an experimentally acidified Bake (pH 4.5) at the Experimental Lakes Area in northwestern Ontario, Canada. Blooms of FGA influenced the energy balance, chemical cycling, physical features, and biological conditions in the littoral zone. Photosynthetic capacity of the FGA, dominated by Zygogonium, was greater than that of acidified epilithon, the normally dominant littoral algal association, partially offsetting acidification-induced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…The characteristic proliferation of filamentous green algae in the littoral zones of anthropogenically acidified lakes (Turner et al 1995;Vinebrooke et al 2001) also likely contributed to pigment-inferred increases in post-industrial algal abundance in the acidified Killarney lakes. In particular, increased sedimentary chl b concentrations in Acid Lake, OSA Lake, George Lake, and Bell Lake after 1900 suggested that green algae became more abundant in these lakes following the onset of acid deposition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristic proliferation of filamentous green algae in the littoral zones of anthropogenically acidified lakes (Turner et al 1995;Vinebrooke et al 2001) also likely contributed to pigment-inferred increases in post-industrial algal abundance in the acidified Killarney lakes. In particular, increased sedimentary chl b concentrations in Acid Lake, OSA Lake, George Lake, and Bell Lake after 1900 suggested that green algae became more abundant in these lakes following the onset of acid deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Acid rain, climate warming, and increased ultraviolet-B (UVB; 280-320 nm wavelength) irradiance impact biodiversity of naturally species-poor communities in boreal lakes, which may reduce or destabilize vital ecosystem functions, such as primary production (Schindler 1995). For example, experimental acidification of boreal lakes caused significant loss of algal species, resulting in increased temporal variability of primary production (Turner et al 1995;Findlay et al 1999). However, primary production is not suppressed by experimental acidification because acid-tolerant species compensate for the extirpation of acid-sensitive competitors Klug et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The abundance of metaphyton is especially notable because it has been common during the 10-year period of the MERP project (Hosseini and van der Valk 1989b), but it is rare in the unmanipulated marsh (Goldsborough and Robinson 1996). Despite being commonly reported to flourish in response to anthropogenic acidification (Turner et al 1995) and eutrophication (Eiseltovh and Pokorn2~ 1994), relatively little is known of the ecological requirements of metaphytic algae. These results demonstrate that algae can be major contributors to total primary production in freshwater wetlands.…”
Section: The Significance Of Algal Primary Productionmentioning
confidence: 99%